Peningkatan Kemampuan Komunikasi Matematika MelaluiMetode Problem Based Learning Pada Siswa Kelas VIISemester Ganjil SMP Negeri 2 Banyudono Tahun Ajaran2015/ 2016 - KHUSZEIMAH, NUR, Dr. Sumardi, M.Si, Sri Rejeki, M.Pd, M.Sc (2016)
This study aims to improve the mathematics communication skill of students at grade VII F SMP Negeri 2 Banyudono in the academic year 2015/ 2016 through Problem Based Learning method. This research is a classroom action research.The data collection was conducted through observation, test, field notes and documentation. The data analysis technique involving three stages which were reduction of the data, presentation of the data and deriving the conclusion. For the validity of the data, it was used the triangulation technique. The Results showed that there was increase of students mathematics communication skill, viewed from the aspects of: 1) speaking: expressing mathematical ideas through word were by asking, answering and giving a conclusion from 4 students (11.11%) to 20 students (55.55 %), 2) writing: explaining the idea and the situation in writing using the appropriate mathematical symbol, from 8 students (22.22%) to 19 students (52.77%), 3) drawing: stating pictures, graphs, and diagrams and mathematical notations in mathematical ideas, from 10 students (27.78%) to 22 students (61.11%), 4) convey the concept: demonstrating and presenting the mathematical ideas presenting mathematical ideas and formulate a definition, from 4 students (11.11%) to 19 students (52.78%). Based on the analysis, it can be concluded that above conclude that the implementation Problem Based Learning method can improve students' mathematics communication skill.